2016
DOI: 10.15537/smj.2016.9.14519
|View full text |Cite
|
Sign up to set email alerts
|

Non-therapeutic infant male circumcision

Abstract: Objectives:To review the evidence of the benefits and harms of infant male circumcision, and the legal and ethical perspectives of infant male circumcision.Methods:We conducted a systematic search of the literature using PubMed, EMBASE, and the Cochrane library up to June 2015. We searched the medical law literature using the Westlaw and Lexis Library law literature resources up to June 2015.Results:Male circumcision significantly reduced the risk of urinary tract infections by 87%. It also significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…A relatively high proportion of hrHPV types in young women in SSA, are not covered by currently available HPV vaccines [31,50] which supports early initiation of cervical screening for all sexually active women living with HIV irrespective of age as recommended by WHO and ASCO [48,51]. A study from Saudi Arabia showed that male circumcision may play role in reduction of HPV infection, penile cancers and cervical cancer among women with circumcised partners [52]. Screening for anal cancers is not routinely recommended, although some experts suggest that this might be effective [53,54].…”
Section: Primary and Secondary Preventionmentioning
confidence: 99%
“…A relatively high proportion of hrHPV types in young women in SSA, are not covered by currently available HPV vaccines [31,50] which supports early initiation of cervical screening for all sexually active women living with HIV irrespective of age as recommended by WHO and ASCO [48,51]. A study from Saudi Arabia showed that male circumcision may play role in reduction of HPV infection, penile cancers and cervical cancer among women with circumcised partners [52]. Screening for anal cancers is not routinely recommended, although some experts suggest that this might be effective [53,54].…”
Section: Primary and Secondary Preventionmentioning
confidence: 99%
“…1 In view of the high prevalence of circumcision worldwide, where it is estimated that one-third of men are circumcised, preputial skin removed during surgery is widely available and is generally discarded as biological waste. 2 However, other biological materials discarded constantly after surgical procedures have shown their relevance for therapeutic applications in various research areas. Among them are the collection of adult dental pulp stem cells, 3 the use of amniotic membrane as a support for skin substitutes 4 and the procurement of umbilical cord and placenta hematopoietic stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…I have read Dr. Alkhenizan and Dr. Elabd systematic review on circumcision 1 in its entirety and with great interest. A narrative overview to gather evidence from previous secondary literature into an accessible and usable document is useful to aid healthcare practitioner 2 and I wish there will be more literature in an overview format to aid healthcare practitioners.…”
mentioning
confidence: 99%
“…Among his claims are that circumcision is unethical and unlawful and that there are no reduction of human papilloma virus among circumcised individuals 6 as opposed to your review which showed a 43 % reduction. 1 In light of your current review, what are the merits or claims of the above contrarian view? Is there any validity to such a claim?…”
mentioning
confidence: 99%
See 1 more Smart Citation